2018
DOI: 10.1063/1.5017217
|View full text |Cite
|
Sign up to set email alerts
|

Bi2O2Se nanosheet: An excellent high-temperature n-type thermoelectric material

Abstract: Motivated by the recent synthesis of an ultrathin film of layered Bi2O2Se [Wu et al., Nat. Nanotechnol. 12, 530 (2017); Wu et al., Nano Lett. 17, 3021 (2017)], we have systematically studied the thermoelectric properties of a Bi2O2Se nanosheet using first principles density functional theory combined with semiclassical Boltzmann transport theory. The calculated results indicate that the Bi2O2Se nanosheet exhibits a figure of merit (ZT) of 3.35 for optimal n-type doping at 800 K, which is much larger than the Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
65
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 28 publications
10
65
0
1
Order By: Relevance
“…[13][14] The ultrathin thickness may also greatly enhance thermoelectric properties. 15 Inspired by the synthesis of Bi2O2Se sheets, attentions were also paid to the related class of bismuth oxychalcogenides such as Bi2O2Te and Bi2O2S, [16][17] which were predicted to possess intriguing piezoelectricity and ferroelectricity. 17 They have adjustable bandgaps in a range between 0.2 eV and 1.5 eV, [17][18][19] and have little mismatched lattice parameters, yielding their outstanding contributions to the 2D material family.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14] The ultrathin thickness may also greatly enhance thermoelectric properties. 15 Inspired by the synthesis of Bi2O2Se sheets, attentions were also paid to the related class of bismuth oxychalcogenides such as Bi2O2Te and Bi2O2S, [16][17] which were predicted to possess intriguing piezoelectricity and ferroelectricity. 17 They have adjustable bandgaps in a range between 0.2 eV and 1.5 eV, [17][18][19] and have little mismatched lattice parameters, yielding their outstanding contributions to the 2D material family.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Bi 2 O 2 Se has excellent air stability with thickness even down to monolayer (ML). Both high carrier mobility and air stability render 2D Bi 2 O 2 Se the very competitive 2D channel material for next‐generation FET …”
Section: Introductionmentioning
confidence: 99%
“…Compared to Bi 2 O 2 Se, the BiCuSeO sample has both lower electrical and thermal conductivity, with higher ZT value with the increased temperature. Furthermore, a recent theoretical study showed great potential for Bi 2 O 2 Se nanosheet as high efficiency thermoelectric materials . The calculated band gap of Bi 2 O 2 Se nanosheet (2.09eV) is significantly larger than that of bulk pristine Bi 2 O 2 Se (0.8 eV), which contributed to its large Seebeck coefficient.…”
Section: Structures and Properties Of Layered Thermoelectric Materialsmentioning
confidence: 96%
“…Crystal structures of layered bismuth oxyselenide a) BiCuSeO; b) Bi 2 O 2 Se. Adapted with permission . Copyright 2018, American Cehmical Society.…”
Section: Structures and Properties Of Layered Thermoelectric Materialsmentioning
confidence: 99%
See 1 more Smart Citation